Компактный импульсный генератор для питания рентгенографического источника; Известия вузов. Физика; Т. 50, № 2 - Ратахин Н. А. Николай Александрович; Федущак В. Ф.; Эрфорт А. А.; Жарова Н. В.; Жидкова Н. А.; Чайковский С. А.; Орешкин В. И. (2007, 2007)
Заглавие с экрана